Effects of Gluten-free Diet on Lipid Profile Risk Factors in Celiac Children. Issue 3 (15th August 2021) - Angi, Alessia; Polidori, Nella; Cerruto, Marina; Chiarelli, Francesco; Mohn, Anna Angelika
Abstract : Many studies raise concerns about the nutritional consequences of gluten-free diet. It has been documented that gluten-free (GF) foods have a higher glycemic index, saturated fats, and lower content of micronutrients determining important health implications. In this retrospective study, we evaluated the change in cardiometabolic risk factors in prepubertal celiac children in remission following different gluten-free diet regimes. Patients using processed GF foods showed a significant increase over time for standard deviation score-total cholesterol, standard deviation score-low density lipoprotein cholesterol, and fasting glycemia. These alterations were not confirmed in patients using naturally GF foods. Therefore, processed GF foods might promote unfavorable alterations of metabolic parameters, especially those associated with increased risk of cardiovascular diseases. Supervision of a dietitian and medical practitioner is recommended to ensure nutritional adequacy and monitoring of cardiovascular risk factors in this population.